Cultivo intercalar de plantas de cobertura na cultura da pimenta-do-reino - Silva, Bruno Eustáquio Cirilo (2020)
Espírito Santo stands out on the national scene as the largest black pepper producer in the country. In this region, the exposed soil is often observed, which predisposes the soil to water erosion and a decrease in the organic matter content. The use of cover crops can provide improvements in the physical and chemical quality of the soil, promoting the sustainability of crops. The objective of this study was to evaluate different species used as cover plants under the physical and chemical attributes of the soil, in black pepper crops located in the northern region of the state of Espírito Santo. The experiment was conducted for three cycles in a commercial black pepper crop of the Bragantina variety, installed in 2014, planted at 3.0 x 2.0 m (1,667 plants ha-1), drip irrigation, located in the municipality of São Mateus, north of Espírito Santo. The experiment was installed in April 2017, with the treatments arranged in randomized blocks, with four replications, totaling 24 experimental plots, using four species of cover plants and another treatment in which there were no cover plants between the lines between the lines. (single cultivation). Crotalaria cover plants (Crotalaria spectabilis), dwarf pigeon pea (Cajanus cajan), millet (Pennisetum glaucum L.) and brachiaria ruziziensis (Brachiaria ruziziensis) were used. Data regarding the fresh and dry mass of cover plants, productivity of black pepper plants, soil physical-hydraulic analysis (available water in the soil, hydraulic conductivity, soil density, aggregate stability, macroporosity, microporosity) were evaluated resistance to penetration in the laboratory and in the field). Leaves of cover plants and black pepper were collected to evaluate the nutrient content and soil samples were collected to evaluate data regarding the chemical attributes of the soil at depths of 0-10 cm and 10-20 cm (pH, P, K, Ca, Mg, Al, H + Al, MO, Zn, Cu, Mn, Fe). The treatment with the brachiaria sequence (BBB) showed the best aggregate stability and hydraulic conductivity. The cover plants promoted a significant increase in the content of organic matter and phosphorus with the use of cover plants. The cultivation of cover crops provided a large production of straw and, consequently, a large accumulation of nutrients, thus being a conservation practice of great importance for the sustainability and profitability of the black pepper crop.